The Influence of Financial Literacy, Financial Inclusion, Marketing Strategy, and Technology on the Development of Culinary MSMEs in Medan Baru District - Silaban, Riski Riama; Lasmaria; Sari, Ike Rukmana; kumalasari, Fauziah (Lembaga Riset Ilmiah, 2025)
Micro, Small, and Medium Enterprises (MSME) cover various sectors such US trade, industry, and services, which together form the foundation of a strong and sustainable economy. The presence of MSME supports economic diversification, reduces economic disparities, and increases the resilience of the country's economy. MSMEs will be able to compete if they are able to implement good management and good marketing strategies and are able to utilize digital information technology well. The development of e-commerce allows MSME to expand their market reach and increase sales. Because currently digital technology is one of the main needs and has become a pattern and lifestyle of today's society, especially for millennials. The purpose of this study is to find out strategic ways to increase the knowledge of MSME actors